Daily hassles and coping dispositions as predictors of psychological adjustment: A comparative study of young unaccompanied refugees and youth in the resettlement country. (May 2014) - Seglem, Karoline B.; Oppedal, Brit; Roysamb, Espen
This study examined daily hassles and coping dispositions in relation to life satisfaction and depressive symptoms among resettled unaccompanied refugees and other youth in the resettlement country. A total of 223 unaccompanied refugees ( M = 20 years) was compared with 609 ethnic minority and 427 majority youth in Norway. Unaccompanied refugees reported higher levels of depressive symptoms, daily hassles and engagement and disengagement coping than the other two groups, but equal level of life satisfaction. Daily hassles and disengagement coping predicted lower life satisfaction and more depressive symptoms across groups. Engagement coping predicted higher life satisfaction in all groups, but not less depressive symptoms among unaccompanied refugees. Multiple mediation analyses showed that daily hassles and coping dispositions partly explained group differences in depressive symptoms, and that at the same level of hassles and disengagement coping, unaccompanied refugees would be significantly more satisfied with life. Findings suggest that interventions to promote more effective coping strategies to handle the many hassles in their daily lives may improve unaccompanied refugees' psychological adjustment and chances to succeed in the resettlement country.